Peningkatan Efektivitas Pembelajaran dengan Moodle sebagai Media Pembelajaran: Metode Literatur - Muhammad Rahmattullah; Monry Fraick Nicky Gillian Ratumbuysang; Maulana Rizky; Achmad Mustofa; Ananda Setiawan (Pendidikan IPS FKIP ULM, 2021)
Increasing the effectiveness of learning is a way to achieve the success of educational development. One way to achieve learning effectiveness is to use learning media to simplify and make the learning process effective. This research aims to reveal as many empirical studies on effectiveness as possible through articles published in international journals to explain to educators the impact of implementing Moodle as a learning media. This research used a literature study method. The results of this study provide an explanation that Moodle can improve student achievement, motivation, communication, interest, discipline and increase self-confidence.